Prediction of the Recurrence of Non-Functioning Pituitary Adenomas Using Preoperative Supra-Intra Sellar Volume and Tumor-Carotid Distance - Chen, Wenli; Wang, Mengqi; Duan, Chengbin; Yao, Shun; Jiao, Haosen; Wang, Zongming; Hu, Bin; Mao, Zhigang; Zhu, Yonghong; Wang, Haijun (Frontiers in Endocrinology, 2021)
Background It is still difficult to estimate the possibility of recurrence of non-functioning pituitary adenomas (NFPAs) currently. Markers like Ki-67 or transcriptional factors rely on post-operative pathology, while few indexes can be used for prediction pre-operatively. Therefore, we aim to investigate the predictive effectiveness of supra-intra sellar volume and tumor-carotid distance based on the measurements derived from pre-operative magnetic resonance imaging (MRI) data. Method Ninety-eight cases of NFPAs were collected with their clinical characteristics and MRI features. Four radiologic indexes were analyzed including intra-sellar tumor volume, supra-sellar tumor volume, maximum horizontal tumor diameter, and inter-carotid distance. The ratio of supra-intra volume and ratio of tumor-carotid distance was measured using 3D Slicer software and the sum of two ratio was defined as the V-D value. The correlation between recurrence and multiple factors was analyzed using univariate and multivariate Logistic regression, Kaplan-Meier analysis, and ROC curves were used to estimate the prognostic performance of radiologic measurements in NFPAs. Result The ratio of supra-intra volume, ratio of tumor-carotid distance and V-D value were significantly correlated with the recurrence of NFPAs. The predictive value of V-D value reached 84.5% with the sensitivity being 83.7% and specificity being 67.3%. The cut-off value of V-D value is 1.53 and the patients with V-D value higher than 1.53 tend to undergo relapse much earlier. Conclusion The V-D value has a predictive value for the recurrence of NFPAs pre-operatively. Patients with higher V-D values will undergo recurrence earlier and should be taken more seriously in terms of surgery and follow-up time.